HUBUNGAN PENGETAHUAN DENGAN PERILAKU IBU HAMIL DALAM MENGKONSUMSI TABLET FE DI PUSKESMAS KALASAN YOGYAKARTA - Anita Liliana; Endang Nurul Syafitri; Melania Wahyuningsih (Jurnal Ilmu Keperawatan Maternitas, 2023)
Background: Anemia case is still concerning in DIY since it increased from 14.85% in 2015 to 16.09% in 2016. Knowledge is correlated with the behavior of an individual because knowledge is an essential domain in shaping a certain behavior.Objectives: To find the correlation between knowledge and behavior of pregnant women in consuming Fe Tablet in the Community Health Centre of Kalasan YogyakartaMethod: This study is an analytical study of correlation with a cross-sectional approach. The subjects were trimester II and III pregnant women. This study employed consecutive sampling as the sampling technique. The instrument was questionnaire. The sample of this study was 56 respondents. The researcher used Kolmogorov-Smirnov in analyzing the data.Results: Most of the pregnant women (55.4%) possessed a sufficient level of knowledge and most of the pregnant women (69.6%) were at a good level of behavior in consuming Fe Tablet. The result of the Kolmogorov-Smirnov Test showed 0.000Conclusion: Statistically there is a significant correlation between knowledge and behavior of pregnant women in consuming Fe Tablet because the p-value was less than 0.05